Green Stereoselective Synthesis and In Silico Anticancer Evaluation of Tetrahydro-β-carboline-Derived Spiro Heterocycles - Mohan, Maneesh; Eldhose, Susan P.; Sudheendranath, Athul; G., Jayasree E.; Deepthi, Ani (Synthesis, 2023)
A green stereoselective synthesis of spiroheterocycles incorporating a spirooxindole and a 1,2,3,4-tetrahydro-β-carboline (THβC) are demonstrated here by the one-pot, three-component reaction of THβC, isatins, and chalcones. Operational simplicity and chromatography-free isolation are the highlights of the reaction which resulted in densely substituted spiroheterocycles with four-contiguous stereocenters in excellent yields. The activity of the compounds as anticancer agents was studied in silico against MDM2 and PLK1 target proteins and they show excellent binding interactions compared to reference drugs.
Keywords: [3+2] cycloaddition; azomethine ylide; 1,2,3,4-tetrahydro-β-carboline; spiroheterocycles